The city in the world of the future - Hellman, Hal, 1927- (New York : M. Evans; distributed in association with Lippincott, Philadelphia, 1970)
Discusses the definition of a city and examines how limited resources and a growing population will influence the way cities are planned and built in the future.
Bibliography: p. 178-181.
Keywords: City planning; City planning